A Review of E-Government Practices in the Age of Digitalization - Fazil, Abdul Wajid; Hakimi, Musawer; Aslamzai, Sebghatullah; Quchi, Mohammad Mustafa (PT. Riset Press International, 2024)
In the era of digitalization, this study comprehensively reviews e-government practices, focusing on the European Union member states, with a particular emphasis on Slovakia and the Czech Republic. The purpose of this research is to analyze the impact of public administration digitalization on corruption, utilizing a comparative and correlative research analysis. The study also investigates the clustering of e-government practices in the EU using Gaussian Mixture Models. The methodology employed includes an extensive review of existing literature on e-government maturity models, benchmark frameworks, and national concepts of public administration informatization. Data from authoritative sources such as the Digital Economy and Society Index (DESI), E-Government Benchmark reports, and national reports, including Slovakia's National Concept of Public Administration Informatization, contribute to a robust analysis. Results reveal the nuanced relationship between public administration digitalization and corruption levels in EU member states. Clustering based on Gaussian Mixture Models provides insights into the diverse landscape of e-government practices. Furthermore, the study compares the digitalization progress of Slovakia and the Czech Republic, shedding light on the challenges and successes of these nations in implementing e-government services. In conclusion, the findings underscore the significance of e-government in shaping transparent and efficient public administrations. Recommendations include fostering international collaboration to share best practices and addressing shortcomings in e-government policy implementation. The research implications extend to policymakers, researchers, and practitioners, offering valuable insights for advancing e-government development. This study contributes to the ongoing discourse on e-government, aligning with the global effort towards sustainable development and digital governance. As governments strive to provide citizen-centric digital services, understanding the intricacies of e-government practices becomes imperative for informed decision-making and policy formulation.